2016
DOI: 10.1016/j.reprotox.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression profiling and functional annotation analysis of their targets modulated by oxidative stress during embryonic heart development in diabetic mice

Abstract: Maternal pregestational diabetes mellitus (PGDM) induces congenital heart defects (CHDs). The molecular mechanism underlying PGDM-induced CHDs is unknown. microRNAs (miRNAs), small non-coding RNAs, repress gene expression at the posttranscriptional level and play important roles in heart development. We performed a global miRNA profiling study to assist in revealing potential miRNAs modulated by PGDM and possible developmental pathways regulated by miRNAs during heart development. A total of 149 mapped miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 66 publications
(112 reference statements)
0
21
0
Order By: Relevance
“…Injection of exosomes isolated from the circulation of diabetic mice into normal pregnant mice reportedly increased the risk of CHD in their offspring [67]. Further studies revealed that diabetic pregnant mice display significant changes in exosomal miRNA profiles compared to normal pregnant mice [73,74]. Additionally, significant differential expression of more than 100 circulating miRNAs, including miR-34a, miR-142-5p, miR-1275, miR-4666a-3p and miR-3664-3p, in the peripheral blood of pregnant women carrying a foetus with abnormal heart development compared to women with normal pregnancy has also been reported [57,75,76].…”
Section: Circulating and Exosomal-derived Mirnas In Pregnant Women Wimentioning
confidence: 99%
“…Injection of exosomes isolated from the circulation of diabetic mice into normal pregnant mice reportedly increased the risk of CHD in their offspring [67]. Further studies revealed that diabetic pregnant mice display significant changes in exosomal miRNA profiles compared to normal pregnant mice [73,74]. Additionally, significant differential expression of more than 100 circulating miRNAs, including miR-34a, miR-142-5p, miR-1275, miR-4666a-3p and miR-3664-3p, in the peripheral blood of pregnant women carrying a foetus with abnormal heart development compared to women with normal pregnancy has also been reported [57,75,76].…”
Section: Circulating and Exosomal-derived Mirnas In Pregnant Women Wimentioning
confidence: 99%
“…For example, a literature survey described that all 12 miRNAs, which have a confirmed role in atrial fibrillation, are modulated by ROS in cardiomyocytes or vascular cells, and target genes involved in electrical and/or structural cardiac remodelling (Lee et al , ). On an experimental level, a global miRNA profiling study in developing hearts showed that SOD1 overexpression could restore all miRNAs significantly altered by maternal pregestational diabetes mellitus, suggesting that oxidative stress might be responsible for dysregulation of miRNAs targeting cardiac development related pathways in offspring of diabetic mothers (Dong et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%
“…The most studied mechanism for miRNAs in pre-gestational diabetes is the potential embryopathy of the offspring, affecting several organs, especially the neural tube and the heart. Existing evidence is based on mouse and in vitro studies (see Table 3) [86,87,88,89,90,91,92,93,94,95].…”
Section: Mirnasmentioning
confidence: 99%